ANALISIS PERBANDINGAN KINERJA KEUANGAN ANTARA BPR KONVENSIONAL DENGAN BPR SYARIAH DI INDONESIA - ROSIDAH -; ARDI PAMINTO; RIZKY YUDARUDDIN (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
The objectives of this researct to make compare the finance performance of BPR Conventional and Islamic BPR in Indonesia in the period 2013-2015 by using financial ratios. Financial ratios are used consisting of ROA, ROA, LDR and CAPITAL. The  data used in this study was obtained from the  published financial statements of the year 2013-2015, published by the Financial Services Authority (FSA). after passing through purposive sample stage, the sample is feasible to use a total of 77 samples, 46 and 31 Conventional BPR and Islamic BPR. The  analysis  technique  used  to  compare  the  financial  performance Conventional BPR BPR Syariah is a method independent sample T-test.The analysis conducted shows that there are differences signifkan for each financial ratio between Conventional BPR and BPR in Indonesia.Keywords: ROA, ROA, LDR, CAPITAL, Financial Performance